The Role of Parents in the Formation of Children's Religious Identity Based on Human Fitrah: Study of Takhrij Hadith - Safitri, Saffanah Ulya; Fitriani, Fitriani; Munawar, Misbahul (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the role of parents in the formation of children's religious identity based on human nature. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is hadith science, while the material object is the hadith of the role of parents in the formation of children's religious identity based on human nature in Bukhari's narration No. 1385. The results and discussion show that parents have a significant role in directing children's Fitrah. This is because the parenting pattern of parents determines the direction of the child's religious identity. This study concludes that parents should continue to adopt Islamic values in their children's education from an early age, as well as the importance of collaboration between family, school and society in shaping children's spiritual and moral development. The originality of this research lies in the integration of hadith analysis with contemporary educational challenges, providing a comprehensive perspective in maintaining the religious identity of future generations in the modern era.